PERSINGGUNGAN KEWENANGAN POLRI DAN KPK DALAM PENANGANAN TINDAK PIDANA KORUPSI: ANALISIS YURIDIS - Yusuf DM, Mohd.; Nopen, Nasib; Hidayah Fatriah, Syarifah; Sitohang, Ramlan; Hamide, Hamide; Pratama, Dio Yulio; Sahfana, Natasya Sri; Nahda, Sayyidah; Habeahan, Irwanto; Wahyudi, Eka; Andrika, Muhammad Reyhan; Danu, Robby Raman (Universitas Labuhanbatu, 2025)
This article examines the overlap of authority between police investigators and the Corruption Eradication Commission (KPK) in handling corruption cases. Using a normative juridical approach, the study analyzes the relevant legal frameworks governing both institutions, including Law No. 8 of 1981 on the Criminal Procedure Code, Law No. 2 of 2002 on the Indonesian National Police, and Law No. 19 of 2019 on the Corruption Eradication Commission. The findings reveal overlapping jurisdictions that may create conflicts in investigative practice, particularly in relation to coordination, supervision, and the execution of institutional mandates. To address these challenges, the article proposes several measures, such as strengthening mechanisms of coordination and supervision, as well as drafting clearer and more binding implementing regulations. These efforts are expected to improve the effectiveness and efficiency of anti-corruption law enforcement, while also enhancing public trust in the integrity of Indonesia’s criminal justice system. Keywords: Investigator, Police, Corruption Eradication Commission